Development of Gartic Platform as Arabic Learning Media Based on Interactive Quiz at Integrated Islamic Elementary School - Ardinal, Eva (UIN Mahmud Yunus Batusangkar, Indonesia, 2024)
The development of technology in this era of globalization is indispensable in the world of education. Many free platforms provide various applications to create interactive learning media, including the Gartic platform. This platform provides games in the form of drawing quizzes that many people can follow. This research aims to develop the gartic platform as an interactive Arabic learning media and foster students’ interest in learning to increase knowledge in an exciting and not boring way. This research method uses the development method (research and development) using the 4D model (Define, Design, Develop, and Disseminate). The results of this study explain that the gartic platform can improve the learning achievement of Integrated Islamic Elementary School students, with evidence that students can memorize more than a thousand Arabic vocabulary. This study concludes that the Gartic platform can help teachers create interactive quizzes so students feel happy learning Arabic. The limitation of this study is that researchers only researched Integrated Islamic Elementary School students where the use of this platform must be modeled first and needs supervision by teachers. For this reason, researchers hope that future researchers can further develop this platform at a higher education level.